2019
DOI: 10.7287/peerj.preprints.27587v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gender and other potential biases in peer review: Analysis of 38,250 external peer review reports

Abstract: Background The Swiss National Science Foundation (SNSF) supports fundamental and use-inspired research in all disciplines. Peer reviewers assess the proposals submitted to the SNSF. We examined whether the gender of applicants and reviewers and other factors influenced the summary scores awarded. Methods We analysed 38,250 reports on 12,294 grant applications across all disciplines 2006 to 2016. Proposals were rated on a scale from 1 (=worst) to 6 (=best) by 26,836 reviewers. We used linear mixed effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In extreme cases, the grant review program can be more costly than simply allocating small grants to each applicant, as in the case of the NSERC grant system of 2008 (3). In addition, the allocation of grants has shown to suffer from various biases, such as the composition of the grant panel (4), gender and geographical location (5), group based dynamics personality triumphing over other qualitative factors (6)(7)(8), and socio-psychological factors such as group dynamics and personality traits triumphing over other qualitative factors (8,9). Overall, selection results are only weakly predictive of future performance (10).…”
Section: Introductionmentioning
confidence: 99%
“…In extreme cases, the grant review program can be more costly than simply allocating small grants to each applicant, as in the case of the NSERC grant system of 2008 (3). In addition, the allocation of grants has shown to suffer from various biases, such as the composition of the grant panel (4), gender and geographical location (5), group based dynamics personality triumphing over other qualitative factors (6)(7)(8), and socio-psychological factors such as group dynamics and personality traits triumphing over other qualitative factors (8,9). Overall, selection results are only weakly predictive of future performance (10).…”
Section: Introductionmentioning
confidence: 99%
“…The Swiss National Science Foundation (SNSF) found that reviewers nominated by applicants tended to score their applications higher than reviewers selected by the Foundation. It concluded that their peer‐review mechanism might be subject to bias and stopped requiring reviewer proposals by applicants [preprint: ].…”
Section: The Introduction Of Peer Reviewmentioning
confidence: 99%
“…Women, especially those from underrepresented groups such as Black, Indigenous, and people of color, bear higher burdens of service-related activities in what is commonly known as a "minority tax" (Rodríguez et al, 2021;Williamson et al, 2021). Conversely, in metrics that are traditionally rewarded in academia, such as prestigious international awards (Meho, 2021) and peerreviewed grants and publications (Day et al, 2020;Severin et al, 2020), women are often disadvantaged. For example, a cross-sectional analysis of peer review reports from the Swiss National Science Foundation revealed that grants submitted by male applicants scored more favorably than those submitted by female applicants (Severin et al, 2020).…”
Section: Editorial On the Research Topic Women In Chemical Engineeringmentioning
confidence: 99%